The relationship between peripheral neuropathy and efficacy in second-line chemotherapy for unresectable advanced gastric cancer: a prospective observational multicenter study protocol (IVY) - Tanioka, Hiroaki (BMC Cancer, 2019)
BACKGROUND: Paclitaxel is used in second-line conventional chemotherapies to manage patients with unresectable advanced gastric cancer (GC). Paclitaxel-induced peripheral neuropathy is a known adverse event leading to treatment discontinuation. Additionally, oxaliplatin which causes irreversible peripheral neuropathy is now commonly used in first-line chemotherapy for advanced GC in Japan. Thus, examining the incidence of peripheral neuropathy with paclitaxel after oxaliplatin is necessary to improve the quality of life and outcomes of patients with advanced GC in the second-line treatment setting. METHODS: This prospective observational multicenter study, (which we named IVY study), will evaluate the degree of chemotherapy-induced peripheral neuropathy (CIPN) and the efficacy of second-line chemotherapy for unresectable advanced GC. A patient neurotoxicity questionnaire (PNQ) and the Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (FACT/GOG-Ntx) will be used to assess CIPN during the second-line treatment. The key eligibility criteria are as follows: 1) unresectable or recurrent GC histologically confirmed to be primary adenocarcinoma of the stomach, 2) age over 20 years, 3) Eastern Cooperative Oncology Group performance status score of 0–2, 4) written informed consent following full study information is provided to the patient, 5) progression or intolerance for first-line chemotherapy comprising fluorinated pyrimidine and platinum anticancer drugs (cisplatin or oxaliplatin) for advanced GC. 6) presence of evaluable lesions as confirmed using a computed tomography (CT) or magnetic resonance imaging. A total of 200 patients is considered to be appropriate for inclusion in this study. DISCUSSION: The results of this study will provide some information on CIPN with the sequential usage of oxaliplatin as first-line chemotherapy to paclitaxel as second-line chemotherapy in clinical practice. TRIAL REGISTRATION: This trial is registered in the University Hospital Medical Information Network’s Clinical Trials Registry with the registration number UMIN000033376 (Registered 11 July 2018).